(untitled) (Medical Forum Monthly, 2023)
Objective: Posterior urethral distraction defects are frequently related with pelvic fracture with prevalence varies from 5% to 10%. It remains a surgical difficulty in reconstructive urology. Therefore, the current investigation mainly focused on the urinary and sexual outcomes after anastomotic urethroplasty performed for posterior urethral distraction defects. Study Design: A retrospective study Place and Duration of Study: This study was conducted at the Department of Urology, Federal Polyclinic Hospital, Islamabad from January 2019 to December 2022. Methods: This study was conducted on 24 male patients aged 15-63 years with distraction defects. All the patients underwent anastomotic urethroplasty and suprapubic cystostomy. Cystourethroscopy and retrograde urethrogram were performed for preoperative evaluation of the patients. Results: A total 24 distraction defect patients were categorized into two groups: Group-I (primary surgery) and Group-II (redo surgery). About 20 (83.3%) patients underwent surgery for the first time (group-I). In 7 patients, a perineal approach without pubectomy was performed, as well as an inferior pubectomy in 11 patients. Due to a lengthier deformity, a transpubic approach was used on two patients in the primary group. In group-II, a perineal approach with inferior pubectomy was used in two patients whereas the remaining two underwent transpubic urethroplasty. The overall success rate was 91.7% whereas the anastomotic urethroplasty without any ancillary procedures was 83.3%. Conclusion: The present study found that anastomotic urethroplasty is the ideal treatment for posterior urethral distraction defects. Most of the patients were treated using a transperineal technique, although a few required a transpubic approach, with satisfactory outcomes.